2019
DOI: 10.7752/jpes.2019.s2070
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Purpose: to identify the optimal load parameters in the process of power training of Mixed Martial Arts athletes with a wrestling style on the basis of studying adaptive and compensatory body reactions in conditions of intense muscular activity of different intensity and volume of work.Material: We examined 40 sportsmen aged (21 ± 0.8), who participated in Mixed Martial Arts fights during the last (2.0 ± 0.3) years and used predominantly a wrestling style of fighting. The athletes were divided into 2 groups: g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
0
13
0
8
Order By: Relevance
“…На основі результатів багаторічних досліджень, спрямованих на вивчення адаптації серцево-судинної системи спортсмена до тренувальних та змагальних навантажень, стало можливим виявити об'єктивні ознаки порушення функціонального стану серцево-судинної системи спортсменів різної спеціалізації. Оптимальне, раціональне навантаження значною мірою позитивно впливає на стан серцево-судинної системи [9,10].…”
Section: стан серцево-судинної системи кваліфікованих спортсменок з настільного тенісу на етапі змагальної діяльностіunclassified
“…На основі результатів багаторічних досліджень, спрямованих на вивчення адаптації серцево-судинної системи спортсмена до тренувальних та змагальних навантажень, стало можливим виявити об'єктивні ознаки порушення функціонального стану серцево-судинної системи спортсменів різної спеціалізації. Оптимальне, раціональне навантаження значною мірою позитивно впливає на стан серцево-судинної системи [9,10].…”
Section: стан серцево-судинної системи кваліфікованих спортсменок з настільного тенісу на етапі змагальної діяльностіunclassified
“…Mixed martial arts (MMA) is a sport growing in popularity around the world. The competitors must be comprehensively prepared in many aspects of physical fitness ( Chernozub et al, 2019 ). Professional bouts consist of three or five 5-minute rounds, whilst amateur bouts are 3 × 3-minute rounds, with the winner determined by a referees’ decision after the allotted time or the fight won ahead of time by knockout, technical knockout, submission, or disqualification ( Rainey, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of training loads together with frequent aggressive strategies aimed at body mass reduction force coaches to employ a large array of biomarkers to streamline the training process ( Kasper et al, 2019 ; Kirk et al, 2021 ). A better understanding of reaction to exercise helps avoid overtraining and optimize the training by recognizing athletes’ individual adaptive and compensatory responses ( Chernozub et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Leading experts in sports and physical training ( James et al, 2016a ; James et al, 2016b ; Kirk et al, 2021 ; Tota & Wiecha, 2022 ) have recently showed great interest in optimizing the system of integrated control of athletes’ adaptation processes in mixed martial arts (MMA) to increase the body functional reserves, to improve the mechanisms of training activity correction, and to maximize performance in the shortest possible time. The complexity of the process of developing an optimal set of criteria for assessing adaptive body changes of MMA athletes is connected with taking into account their individual characteristics, level of training, the style of fighting, and parameters of training load regimes used during training ( Matthews & Nicholas, 2017 ; Slimani et al, 2017 ; Chernozub et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The wide and diverse range of techniques, methods, and principles of training activities used by athletes, depending on the style of fighting in mixed martial arts, raises a number of controversial issues among experts on determining effective training load parameters and correction mechanisms ( Del Vecchio & Franchini, 2011 ; Chernozub et al, 2019 ; Kirk et al, 2021 ). The search for new ways to improve the training of athletes of strike fighting style requires the development of explosive strength and endurance, and a constant increase in adaptive reserves due to intra-muscular and intermuscular coordination and energy efficiency of muscle activity in anaerobic training load regime ( James et al, 2016a ; James et al, 2016b ; Futorniy et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%